Complete renal response at 12 months after induction therapy is associated with renal relapse-free rate in lupus nephritis: a single-center, retrospective cohort study. (April 2019) - Ichinose, K; Kitamura, M; Sato, S; Eguchi, M; Okamoto, M; Endo, Y; Tsuji, S; Takatani, A; Shimizu, T; Umeda, M; Fukui, S; Sumiyoshi, R; et al.
Background: Lupus nephritis (LN) is a major risk factor for overall morbidity and mortality in systemic lupus erythematosus (SLE). Methods: We retrospectively analyzed cases of proliferative and membranous LN patients who underwent a renal biopsy at our hospital in 1993–2016. We analyzed the association between complete renal response (CR) rates at 12 months after induction therapy and predictive factors for CR and their association with renal flares. Results: Of the 95 cases analyzed, we were able to track the therapeutic responses of 81 patients at 12 months after their induction therapy. The median follow-up duration after renal biopsy was 51 months (interquartile range: 16.5–154.5 months). The Cox proportional hazards model showed that, compared to not attaining CR at 12 months, the attainment of CR at 12 months was correlated with being free from renal flares. The multivariate logistic analysis revealed that the predictive factors for CR at 12 months were the anti-La/SSB antibodies (U/ml) (odds ratio (OR) 1.22, 95% confidence interval (CI) 1.01–1.63, p = 0.0220), blood urea nitrogen (BUN) (OR 0.68, 95% CI 0.44–0.90, p = 0.00048) and serum β2 microglobulin (MG) (OR 0.26, 95% CI 0.06–0.74, p = 0.00098) levels. Conclusions: Among LN patients, being free from renal flares was associated with attaining CR at 12 months after induction therapy. Anti-La/SSB antibodies were a positive predictive factor, and BUN and serum β2MG levels were negative predictive factors of CR at 12 months.